Juvenile idiopathic inflammatory myopathies with anti‐3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase antibodies in a Chinese cohort. (1st May 2021) - Hou, Ying; Shao, Kai; Zhao, Bing; Dai, Tingjun; Wang, Qinzhou; Zhao, Yuying; Yan, Chuanzhu; Yan, Yaping; Ma, Xiaotian; Li, Wei
Abstract: Aims: To characterize the clinical and histopathological characteristics and treatment outcomes of juvenile idiopathic inflammatory myopathies (JIIMs) with anti‐3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase (HMGCR) antibodies in a Chinese cohort. Methods: We detected anti‐HMGCR antibodies in a series of Chinese JIIM by ELISA and indirect immunofluorescence assay on HEK293 cells, and summarized the clinical findings of these anti‐HMGCR antibody‐positive patients. Results: Of 32 JIIM patients, 5 (15.63%) were found to be anti‐HMGCR antibody‐positive. The disease duration was 1.20 ± 0.45 months. Statin exposure was not found. Four patients had skin lesions, while typical pathological features of dermatomyositis such as perifascicular atrophy or myxovirus resistance protein A expression were not found. The mean creatine kinase level was 16771.60 U/L. Among the four patients who received long‐term (10.46 ± 1.42 years) follow‐up, three exhibited favorable outcomes with prednisone and additional immunosuppressants. Conclusions: Our study indicates that anti‐HMGCR antibodies may not be rare in Chinese JIIM. These anti‐HMGCR‐positive JIIMs were characterized by acute onset, substantially elevated creatine kinase level, and skin lesions without perifascicular changes in muscle pathology. The treatment outcome is generally favorable with the combination of steroid and immunosuppressant. Abstract : Anti‐HMGCR antibody may not be rare in Chinese juvenile idiopathic inflammatory myopathy (JIIM). These anti‐HMGCR‐positive JIIMs were characterized by acute onset, high creatine kinase level, and skin lesions without perifascicular changes in muscle pathology. The treatment outcome is generally favorable with the combination of steroid and immunosuppressant. Anti‐HMGCR antibody testing should be seen as routine test for juvenile patients.